Top 10 strangest animals - Maloney, Brenna (New York : Scholastic Inc., 2025)
"There are so many strange animals! Some look like trees or plants. Some live in the sea and can fly. Some can even regrow their body parts! Learn all about the strange amphibians, birds, insects, mammals, and reptiles in our wild world. Count down from 10 to 1 and discover which one is the absolute strangest!"--
Ages 5-7
Grades K-1